Pengaruh Peran Kepemimpinan dan Komitmen Organisasi terhadap Kepuasan Kerja Guru - Mahmudin Mahmudin; Imas Komariyah (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2019)
This study aims to know, examine and analyze the influence of leadership role and commitment to job satisfaction in Vocational High School (SMK) Serang City, Serang District and Tanggerang District. The method used in this research is quantitative method of research sample using random sampling at 121 population with 92 respondents. Instrument test results show all statements of the three variables are declared valid. Analysis of verification using path analysis method (Path Analysis). The result of this research conclude that there are positive and significant influence of leadership role to job satisfaction, and there is positive and significant influence of Commitment to job satisfaction. Coefficient Determination (R2) value of leadership role and commitment to job satisfaction equal to 0,445% or 45,5%. And the value outside the model (errovar) of 0.555% or 55.5%.